Effect of Surfactants upon the Acid Catalyzed Hydrolysis of Phenyl Urea - K. SAR, SANTOSH; KANT PANDEY, PIYUSH; SHARMA, RICHA (Asian Journal of Chemistry, 2010)
The kinetics of acidic hydrolysis of phenyl urea in micellar media have been studied. The cationic (cetyl trimethyl ammonium bromide, cetyl pyridinium chloride), anionic (sodium lauryl sulphate) and non-ionic (Triton -X-100, Brij-35) surfactants have been used. The results indicate that the presence of micelles enhance the rate of reaction. Kinetic studies show that the reaction obeyed first order kinetics. The rate surfactant profiles can be explained well by psuedo phase ion exchange model.